Hubungan Sikap Ilmiah Dan Keterampilan Proses Sains Siswa Kelas V SD - Laily, Dhiyan Nur; Suryani, Ela (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine whether there is a relationship between scientific attitude and science process skills of fifth-grade students in Islamic elementary schools in the West Ungaran District. The study uses a quantitative approach with a correlational method, designed to test the relationship between two variables in an educational phenomenon. Data were collected through scientific attitude questionnaires and science process skills tests that had met validity and reliability criteria. Data analysis was carried out using the Pearson Product Moment correlation test. The analysis results show a correlation coefficient of 0.245 with a significance value of 0.006 (< 0.05). These findings indicate a positive and significant relationship between scientific attitude and science process skills, thus the alternative hypothesis (Ha) is accepted. Based on the guidelines for interpreting correlation coefficients, the value of 0.245 falls into the weak relationship category. Thus, it can be concluded that scientific attitude has a positive relationship with students' science process skills, although the level of the relationship is considered low.